ARAHAN PEMANFAATAN LAHAN PADA KAWASAN LINDUNG BERBASIS SISTEM INFORMASI GEOGRAFIS SEBAGAI UPAYA PENGUATAN EKONOMI DI KABUPATEN ENREKANG - Heryanto, Heryanto; Nuddin, Andi; Halimah, Andi Sitti (Jurnal Pendidikan Teknologi Pertanian, 2017)
Increased economic growth slowly but surely could encourage the opening of uncontrolled new lands, decline in the function of protected areas that could threaten the sustainability of agricultural production in the area. This study aims to minimize degradation of protected area function in Enrekang Regency through mapping of protected area based on geographic information system and overlay technique. The results showed that the referral of protected area function was spread in 12 districts with an area of 181,888.45 Ha, as a protected function area, buffer zone, annual cultivation area, as well as cultivation area of annual crops and settlement. Of these areas, approximately 35,834.03 Ha are suitable for land use in protected and unsuitable areas 45,256,76 Ha. The referral of protected area functionÂ  is expected to suppress inappropriate land use so that the legal access of the community in this area is needed, to manage and utilize the land in increasing their economic level while maintaining the sustainability and preventing the destruction of the protected area.